Comparative structure of starches from high-amylose maize inbred lines and their hybrids. (January 2016) - Lin, Lingshang; Guo, Dongwei; Zhao, Lingxiao; Zhang, Xudong; Wang, Juan; Zhang, Fengmin; Wei, Cunxu
Abstract: High-amylose maize starch is of interest because of its health benefits and industrial uses. Hybrid maize is widely grown for the practical and economical value of heterosis. However, starch structure of high-amylose hybrid maize has seldom been reported compared with that of high-amylose inbred maize. In this study, structure of starches from high-amylose maize inbred lines and their hybrids was investigated and compared. Starch granule became smaller in size and more spherical, oval or elongated in shape with increasing amylose content. Hybrid maize starch had lower amylose content and long branch-chain of amylopectin and higher short branch-chain and branching degree of amylopectin than inbred maize starch. Inbred maize starch had B-type crystalline structure with low relative crystallinity, but hybrid maize starch had CB -type crystalline structure and high relative crystallinity. Hybrid maize starch had lower degree of order at a short-range scale on the edge of starch granule than inbred maize starch. Hybrid maize starch had higher double helix content and lower amorphous starch than inbred maize starch. Hybrid maize starch had higher peak intensity and longer Bragg spacing of lamellar structure than inbred maize starch. Hybrid maize starch had lower gelatinization temperature and higher gelatinization enthalpy and swelling power than inbred maize starch. The different structural properties of starches had significant correlation. Graphical abstract: Highlights: Starch structure was compared between high-amylose maize inbred and hybrid lines. Starch granules became smaller and more spherical with increasing amylose content. Hybrid maize had lower amylose content and amorphous starch than inbred maize. Hybrid maize had CB -type crystallinity and inbred maize had B-type crystallinity. Hybrid maize had higher double helix and lamellar peak intensity than inbred maize.